Interest of manual vacuum aspiration in the management of incomplete abortion at the district hospital of ndjamena south, chad (Bangladesh Journal of Medical Science, 2016)
Background: abortion is one of the main causes of maternal mortality and morbidity in Chad. Objective: The aim of this work was to evaluate the interest of manual vacuum aspiration (MVA) in the management of incomplete abortion.Methods: This was a prospective and descriptive survey for five months from March 5th 2014 to August 05th 2014 conducted at the district hospital of N Djamena South. All women admitted for incomplete abortion were included. Before including the patient in our investigation her consent should be gotten after some explanations on the necessity of the survey have been given. Data analysis has been done by EPI INFO 3.5.1.Results: we enumerated 154 incomplete abortions among 2327 pregnancies registered at the prenatal consultation service and emergency unit. That gave the prevalence of 06.6%. The majorities of our patients had spontaneous abortion (96.1%). The time allowed for management was ?12 hours (90.3%). No complication was observedConclusion: MVA is an effective and sure method to evacuate uterus when incomplete abortion is diagnosed.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.572-574